Building anti-fragile organisations risk, opportunity and governance in a turbulent world - Bendell, A. (Gower, 2014)
Every day human organisations fail. Building Anti-Fragile Organisations explores a powerful alternative framework for risk in design and management of human systems. Anti-Fragile organisations, like biological systems, being more than robust actually improve their resilience through being stressed. In the book.